Edukasi Konsep Tata Ruang Dan Kreativitas Menu Terhadap Minat Pengunjung - Nirma Rosalia; Fachrun Nissa; Mega Hasibuan; Herlin Simanullang (Outline Publisher, 2026)
The increasing demand for food and beverages in North Sumatra will undoubtedly create business opportunities for the community. The rapid growth of the food and beverage business is evident in the large number of people engaged in culinary businesses. The increasing demand for food and beverages in North Sumatra will undoubtedly create business opportunities for the community. The rapid growth of the food and beverage business is evident in the large number of people engaged in culinary businesses. Individual economic stability is a crucial prerequisite for achieving well-being and financial independence. The Community Service Program (PKM), entitled Education on Spatial Planning Concepts and Menu Creativity for Visitor Interest aims to increase literacy, interest, and skills in spatial planning concepts through outreach and discussion. This activity involves introducing the basic concepts of personal economic stability and fostering interest in initiating spatial planning concepts and creativity among business owners. These findings indicate that the program has successfully motivated business owners to develop or modify existing concepts to make students feel comfortable purchasing from their stalls. Creativity in exploring food courts based on local wisdom is expressed through interior design inspired by a particular ethnic group, showcasing its distinctive elements. Furthermore, the comfort and ambiance of the food court are key reasons for visitors to visit. This research is highly relevant for several reasons. First, the ever-growing and competitive nature of food courts makes it crucial to understand how to leverage local wisdom to differentiate and attract customers. Second, food courts play an increasingly significant role in business and culture, making it crucial to understand their business practices, including creativity within the food court context. Finally, with increasing globalization and homogenization in the food and beverage industry, emphasizing local wisdom can help maintain cultural and culinary diversity.